The Effect of Different Stocking Densities on Growth and Survival Rate of Giant Prawns (Macrobrachium rosenbergii) in the Biofilter Recirculation System - Tobing, Olaelita L; Rusliadi, Rusliadi; Masjudi, Heri (Jurnal Akuakultur SEBATIN, 2025)
This research aims to determine the effect of different stocking densities on the growth and survival of Giant prawns (Macrobrachium rosenbergii) which are reared using a biofilter recirculation system. This research was conducted from June to July 2024 at the Cultivation Technology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This research used a one-factor Completely Randomized Design (CRD) method with four treatment measures and three replications. The treatment levels applied in this study were stocking density 20 fish/m2, stocking density 40 fish /m2, stocking density 60 fish /m2, and stocking density 80 fish /m2. The results of the study showed that different stocking densities had a significant effect (P<0.05) on the growth performance of Giant prawns. The best treatment was found at a stocking density of 80 fish /m2 which resulted in growth in absolute weight 2.34 g, absolute length 3.96 cm, specific growth rate 2.59%, survival rate was 98.33% and THC value was 20.654×106 cells/mL.